Validation of the Spanish Short Self-Regulation Questionnaire (SSSRQ) through Rasch Analysis - Garzón Umerenkova, Angélica; de la Fuente Arias, Jesús; Martínez-Vicente, José Manuel; Zapata Sevillano, Lucía; Pichardo, Mari Carmen; García-Berbén, Ana Belén (Frontiers in Psychology, 2017)
Background. The aim of the study was to psychometrically characterize the Spanish Short Self-Regulation Questionnaire (SSSRQ) through Rasch analysis. Method. 831 Spaniard university students (262 men), between 17 and 39 years of age and ranging from the first to the fifth year of studies, completed the SSSRQ questionnaire. Confirmatory factor analysis was carried out in order to establish structural adequacy. Afterwards, by means of the Rasch model, a study of each sub scale was conducted to test for dimensionality, adjustment of the sample questions, functionality of the response categories, reliability and estimation of Differential Item Functioning (DIF) by gender and course. Results. The four sub-scales comply with the unidimensionality criteria, the questions are in line with the model, the response categories operate properly and the reliability of the sample is acceptable. Nonetheless, the test could benefit from the inclusion of additional items of both high and low difficulty in order to increase construct validity, discrimination and reliability for the respondents. Several items with differences in gender and course were also identified. Discussion. The results evidence the need and adequacy of this complementary psychometric analysis strategy, in relation to the confirmatory factor analysis to enhance the instrument.